Implementation of Social Reintegration of Children as Inmates After Undergoing Guidance at a Special Guidance Institution for Children Class I in Tangerang - Widodo, Guntarto (Action Research Literate, 2024)
The presence of Law Number 22 of 2022 concerning Corrections is expected to strengthen the concept of social reintegration and also the concept of restorative justice. This concept has actually been alive and in line with the concept of social reintegration which is the goal of the Correctional System. The author uses descriptive analytical methods, namely research that describes and analyzes problems related to the concept or system of prisoner guidance. The results of this study indicate that the rehabilitation process is not only limited to the form of supervision, but the perpetrators' children are also provided with various skills, in addition to the fulfillment of education to take the package chase exam which is given the opportunity to the perpetrators' children. Specifically for the issue of reintegration for child perpetrators, LPKA Class 1 Tangerang City does not only carry out the return or handover of child perpetrators who have completed their detention to their families, but also provides a follow-up monitoring process whether the child perpetrators can adapt to the environment and be accepted openly by the surrounding community, this is in accordance with Law Number 22 of 2022 concerning Corrections. The social reintegration process regulated in the Corrections Law emphasizes the creation of justice, balance, restoration of relationships, legal protection, and guarantees for the human rights of prisoners, children, convicts, foster children, victims, and the community.